Designed multifunctional polymeric nanomedicines: long-term biodistribution and tumour accumulation of aptamer-targeted nanomaterials. Issue 82 (5th September 2018) - Fletcher, N. L.; Houston, Z. H.; Simpson, J. D.; Veedu, R. N.; Thurecht, K. J.
Abstract : We report a novel multifunctional hyperbranched polymer based on polyethylene glycol (PEG) as a nanomedicine platform that facilitates longitudinal and quantitative 89 Zr-PET imaging, enhancing knowledge of nanomaterial biodistribution and pharmacokinetics/pharmacodynamics both in vivo and ex vivo . Abstract : We report a novel multifunctional hyperbranched polymer based on polyethylene glycol (PEG) as a nanomedicine platform that facilitates longitudinal and quantitative 89 Zr-PET imaging, enhancing knowledge of nanomaterial biodistribution and pharmacokinetics/pharmacodynamics both in vivo and ex vivo . Anti-VEGF-A DNA aptamer functionalization increased tumour accumulation by >2-fold in a breast cancer model.